Can Statistical Capacity Building Help Reduce Procyclical Fiscal Policy in Developing Countries? - Tapsoba, Sampawende (IMF Working Papers; Working Paper ;, 2016)
Few papers have attempted to assess the role of 'capacity,' especially in the area of macroeconomic statistics. Consequently, we make an attempt to advance this literature through the construction of a 'statistical capacity building index,' and then test its explanatory power on the cyclicality of government spending. Using panel data from 62 developing countries, we find evidence that improvements in this index are associated with less procyclicality of government spending over the period 1990-2012; with the significance of this relationship dependent upon the quality of administrative and technical capacity of budgetary institutions.